The Relationship Between Resilience and Work Engagement in Dukcapil Employees in The City of Padang Panjang - Suci Anisa; Herio Rizki Dewinda; Ummil Khairiyah (Psycho Holistic, 2023)
This study aims to determine the relationship between resilience and work engagement for dukcapil employees in the city of Padang Panjang. The independent variable in this study is resilience while the dependent variable is work engagement. The measuring tools used in this study are the resilience scale and work engagement. The sampling technique in this study used a saturated sampling technique. The sample in this study were 32 dukcapil employees in the city of Padang Panjang. Test the validity and reliability in this study using Alpha Cronbach technique. The results of the validity coefficient on the resilience scale moved from rix = 0.655 to rix = 0.892 with a reliability coefficient value of α = 0.970 while the results of the validity coefficient on the work engagement scale moved from rix = 0.702 to rix = 0.858 with a reliability coefficient value of α = 0.959. Based on data analysis, a correlation value of 0.680 was obtained with a significance level of 0.000, which means that the hypothesis is accepted. This shows that there is a strong and significant relationship between resilience and work engagement for dukcapil employees in the city of Padang Panjang.